A CLINICAL CASE OF INFECTIOUS ENDOCARDITIS IN A PATIENT WITH MARFAN SYNDROME - Mirzayev A.M; Zubaydullayeva M.T; Saidahmadov S.S.; Makhmudova M.S. (Western European Studies, 2025)
"Infectious endocarditis (IE) is a serious disease characterized by inflammation of the endocardium, most often caused by a bacterial infection. Damage to the heart valves can lead to their dysfunction, embolism, and other serious complications. Timely diagnosis and adequate treatment, including antibiotic therapy and, in some cases, surgery, are crucial for improving outcomes. "In this article, we will look at a clinical case illustrating various aspects of the diagnosis and treatment of IE."
Keywords: infectious endocarditis; diagnosis; treatment